ПЕДАГОГІЧНЕ ТЕСТУВАННЯ ЯК ЗАСІБ МОНІТОРИНГУ ОСВІТИ: УПРАВЛІНСЬКИЙ АСПЕКТ (Педагогіка вищої та середньої школи, 2009)
The article deals with the problem concerning existing possibilities of pedagogical testing while forming monitoring system of education establishments on managers' level.